Phosphatase Dysregulation in Cancer: Signaling Pathways and Therapeutic Opportunities - Maryam Jama; Michael Overduin; Khaled H. Barakat (MedComm – Oncology)
ABSTRACT Phosphatases are increasingly recognized as critical regulators of cancer biology, with important roles in both tumor cells and the tumor immune microenvironment (TIME). These enzymes modulate intracellular signaling pathways that control tumor growth, immune evasion, and metastasis. Although phosphatases were once considered undruggable, recent advances have highlighted their therapeutic potential. Despite growing evidence, phosphatases remain underexplored as drug targets, with no approved therapies to date. This review presents an in‐depth overview of phosphatase classification based on catalytic domain similarities and explores their diverse functions as tumor suppressors, oncogenic drivers, or context‐dependent regulators. We describe how phosphatases such as PTPN6, PTPN22, and DUSPs regulate key pathways like RAS/MAPK and PI3K/AKT in both tumor and immune cells. Additionally, we discuss the role of phosphatases in shaping the tumor microenvironment through exosome secretion. This review highlights current therapeutic strategies, including small molecules and antibodies, and their synergistic effects with kinase inhibitors and immune checkpoint blockade. By summarizing recent advances, this paper underscores the need for deeper mechanistic insights into phosphatase function in cancer and immunity. Understanding these mechanisms will be key to unlocking their potential as novel therapeutic targets in oncology.